Anibal Quijano: a life after a debatable category - Lora Cam, Jorge (2021)
The last 50 years mark the Latin American left because of the debate about the transition to capitalism and Conquest of the State. Period characterized by the avant-gardes and / or intellectuals in possession or not of the best scientific knowledge, decided for the peoples defining the most correct option. In the last two decades many intellectuals have chosen to liquidate the option of taking power - whether it was popular warfare or insurrection - and to assimilate to small changes, electoral triumphs or the quest for the goodness of liberalism. It was, for many, a choice between the del harmful capitalism of neoliberal globalization, dispossession and war, and other liberal, liberalfair, free, stable and efficient capitalism, which would function, free from crises, militarism and war or from far-right outbreaks. For our analysis Wallerstein chooses this second possibility to which Quijano joins, who supports him filling the systemic scheme of that with the concept of coloniality of power; a system already developed by its eclectic master who, for his part, takes up Braudel’s idea of system-world. For both, 2 there is no greater difference between capitalism 400 years ago and the present one it calls «world economy.» Going so far as to say that in the sixteenth century Europe begets world capitalism as we know it now. The «new left» flying guidelines of the Sao Paulo forum were enthusiastic about electoral processes, anti-racist, feminist, minority identitarians, greens, those who defend the freedom of sexual choice in which their spontaneism and lack of cohesionstand out. These historical experiences allow Quijano to say that from the 1960s onwards there was a demand for the democratic selfpreservation of society that assumes it as his own under the name of eurocentrism decoloniality.